Creation and usability testing of a web-based pre-scanning radiology patient safety and history questionnaire set. - Robinson TJ; DuVall S; Wiggins R III (Journal of Digital Imaging, 2009)
Recent advances in technology have significantly changed radiology workflow. The main focus of these changes has been the transition from hard copy film to digital imaging. The next transition will be a 'paperless' transformation. Web-based versions of the current paper-based patient safety and history questionnaires were created using PHP and MySQL. Two rounds of usability testing using volunteers were completed using tablet PCs. Volunteers were comprised of ten individuals. Ages of volunteers ranged from 27 to 60 years, and there were eight males and two females. The majority of users had at least a Master's degree and was considered to have a computer experience level of a programmer. Eighty percent of the users agreed that the web-based questionnaires and tablet PCs were easy to use. Text input through the writing recognition window and scrolling proved to be the least usable sections of the questionnaires. The new web-based system was found to be a very usable system by our participants. The questionnaires were easy to use, easy to navigate, and easy to read. Individual elements such as radio buttons and checkboxes did not fair as well but were due to their small size. Difficulty with the writing recognition interface is an inherent issue with the Windows XP Tablet Edition operating system.